When the theory is not enough - valuation of forest resources with 'efficiency' prices in practice - Huhtala, Anni; Toppinen, Anne; Boman, Mattias (Urban & Fisher Verlag, 2003)
In resource accounting, simple theoretical models built upon efficiency prices have been developed to capture changes in social welfare generated by natural resources. We examine whether changes in market stumpage prices, as proxies for efficiency prices, have actually reflected changes in the physical timber inventories in Finland and Sweden during the past seventy years. Cointegration and unit root tests show that no long-term equilibrium relationships exist between the timber prices and stocks. After identifying a potential reason for the result, the basic theoretical growth model is slightly elaborated to provide a more appropriate framework for measuring net domestic product for the forest sector.
Keywords: Ma; Yl; yhteisintegroitavuus; kantohinnat; metsävarat; forest resources; cointegration; stumpage prices; timber stocks